Image segmentation using probabilistic fuzzy c-means clustering - Pham, T.D. (2001 International Conference on Image Processing, 2001)
A new approach for gray-level image segmentation is presented using a probabilistic fuzzy c-means clustering algorithm. This approach combines the spatial probabilistic information and the fuzzy membership function in the clustering process. The proposed probabilistic fuzzy c-means method can deal effectively with image segmentation in a noisy environment.